Thermal diffusivity measurement of copper selenide using photoflash technique - Mat Daud, Norni Hidayawati (2012)
For several past decades, the studies on the thermal properties of copper selenides (CuSe) have excluded thermal diffusivity even though thermal diffusivity directly reflects the combined effects of thermal conductivity, specific heat and density of materials put together. In this report the research findings of the thermal diffusivity of CuSe as measured by using photoflash technique at the temperature range from 80 K to room temperature are presented. The samples of CuSe which were based on the formula of CuxSe1-x were prepared using solid state method. The first set of the samples was prepared with similar x=0.5 composition, and each of the pellets was sintered at different sintering temperature from 150 to o 275 C for four days. The second and third sets of the samples were prepared by varying Cu composition with x = 0.3, 0.4, 0.5, 0.6, 0.7, and each set was sintered at 250 and o 275 C respectively for four days. XRD micrograph indicates that all the diffraction peaks were indexed to hexagonal CuSe phase for the samples with x = 0.5 and 0.6, and sintered at o 250 C upwards. However,the samples with x = 0.7 and were sintered at o 250 C and o 275 C had cubic Cu2Se single-phase while the sample with x = 0.8 and sintered at o 250 C had Cu2Se phase with two different crystallographic forms of monoclinic and cubic crystal structure. The sample with the most symmetrical crystal structure, which was cubic crystal structure was found to have highest thermal diffusivity while a distorted and the least symmetrical crystal structure was found to have lowest thermal diffusivity. SEM micrograph and density measurement showed that the grain size as well as density increased with the increase of sintering temperature, and with the increase of x up to 0.7. On the other hand the specific heat data showed a decreasing trend with increasing sintering temperature and increasing x. However the specific heat only slightly increased as the sample’s thermal diffusivity measuring temperature increased in the range of 80-300 K,showing that the specific heat was more or less independent of temperature. The grain size that increased with the sintering temperature affected the increased in the measured thermal diffusivity. In the bigger grain size samples, phonons would encounter lesser number of grain boundaries, experiencing a longer apparent mean free path and lower phonon-phonon scattering; the thermal diffusivity inevitably becomes higher. The similar increasing trend of thermal diffusivity was also observed for the samples with the increasing x. The thermal diffusivity was consistently decreased with increasing measuring temperature from 80 to 300 K, for all samples. At the very low temperature, the phonon-phonon relaxation time is very long due to the phonon occupation probability which is very low. When the temperature increases, a higher population of thermally excited phonons is expected causing the number of phonon collisions to increase. Thus lattice scattering lowers the thermal carrier mobility more and more at higher temperature due to the smaller mean free path. Therefore, their ability to transport heat away from the source is less, thus decreasing the thermal diffusivity value of this sample. The thermal diffusivity of the CuSe for all set of samples was in the range of (0.225-5.268) mm2/s at the temperature of 80 K to 300 K.